2021
DOI: 10.1038/s41598-021-93078-y
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of zebrafish cardiovascular and behavioral functions through microfluidics

Abstract: This study proposed a new experimental approach for the vascular and phenotype evaluation of the non-anesthetized zebrafish with representative imaging orientations for heart, pectoral fin beating, and vasculature views by means of the designed microfluidic device through inducing the optomotor response and hydrodynamic pressure control. In order to provide the visual cues for better positioning of zebrafish, computer-animated moving grids were generated by an in-house control interface which was powered by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
2
1
Order By: Relevance
“…Chakraborty et al ( 2011 ) observed that in zebrafish eleutheroembryos, an increase in heart rate induced by CAF (10, 20, and 50 mg.L −1 ) at 72 hpf is associated with a decrease in the expression of vascular endothelial growth factor- a protein involved in the development of heart blood vessels and endothelial muscle development, which results in abnormalities in the heart or in the development of cardiac blood vessels and, consequently, increased heart rate. Contrary to our findings, Subendran et al ( 2021 ) observed a decrease in the heart rate of zebrafish larvae at 5, 7, and 9 dpf when exposed, for 10 min, to 25 mg.L −1 of CAF. The authors suggest that CAF effects on zebrafish heart rate are due to the release of calcium in the cytoplasm, which could lead to cardiac nerve transmission and, consequently, a reduction in heart rate.…”
Section: Discussioncontrasting
confidence: 99%
“…Chakraborty et al ( 2011 ) observed that in zebrafish eleutheroembryos, an increase in heart rate induced by CAF (10, 20, and 50 mg.L −1 ) at 72 hpf is associated with a decrease in the expression of vascular endothelial growth factor- a protein involved in the development of heart blood vessels and endothelial muscle development, which results in abnormalities in the heart or in the development of cardiac blood vessels and, consequently, increased heart rate. Contrary to our findings, Subendran et al ( 2021 ) observed a decrease in the heart rate of zebrafish larvae at 5, 7, and 9 dpf when exposed, for 10 min, to 25 mg.L −1 of CAF. The authors suggest that CAF effects on zebrafish heart rate are due to the release of calcium in the cytoplasm, which could lead to cardiac nerve transmission and, consequently, a reduction in heart rate.…”
Section: Discussioncontrasting
confidence: 99%
“…A sustained increase in heart rate was also induced by a chemical irritant (Roberts et al, 2020). Heart rate can be measured via imaging larvae embedded in agarose (Mann et al, 2010) while more complex features such as blood flow velocity and circulation can be assessed concurrently with behavioral responses (fin beating) using microfluidic set-ups (Subendran et al, 2021). Another biological endophenotype is cortisol levels that can be assayed via radioimmunoassays (Steenbergen et al, 2012) or enzymelinked immunosorbent assays (ELISAs) (Yeh et al, 2013).…”
Section: Open Questions Challenges and Future Prospectsmentioning
confidence: 99%
“…18 Due to accelerating multifaceted learning and memory paradigms developed for adult zebrafish, 19 researchers have extended their studies on larval zebrafish using tiny well-plates, 20,21 petri dishes, 22 and microfluidic devices. 23–29…”
Section: Introductionmentioning
confidence: 99%